Meet the parents - Tenebaum, Nancy; Rosenthal, Jane 1959-; De Niro, Robert 1943-; Roach, Jay 1957- (Universal City, California Universal Studios, 2001)
Male nurse Greg Focker is poised to propose to his girlfriend Pam during a weekend stay at her parents's home. But here's the catch...he needs to ask her father first. Alas, the fur flies as Jack Byrnes, Pam's cat-crazy, ex-CIA father, played hysterically, takes an immediate dislike to her less-than-truthful beau. Greg's quest for approval gets seriously sidetracked as Murphy's Law takes over and a hilarious string of mishaps turns him into a master of disaster and total pariah in the eyes of the entire family?all except for his shell-shocked girlfriend, who can't believe she still loves her one-man wrecking crew.
Music by Randy Newman ; Music supervisor, Randall Poster ; Casting by, Ellen Chenoweth ; Costume designer, Daniel Orlandi ; Edited by Jon Poll ; Production designer, Rusty Smith ; Director of photography, Peter James ; Screenplay by Jim Herzfeld and John Hamburg.
Robert De Niro, Ben Stiller, Blythe Danner, Teri Polo, James Rebhorn, Jon Abrahams, Owen Wilson.
VHS format
In English.
Keywords: Marriage proposals -- New York (State) -- Drama; Man-woman relationships -- Drama; Family life -- Drama; Feature films